2015
DOI: 10.3923/ijss.2015.166.176
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon and Nitrogen Distribution in Particle-size Fractions of Soils Under Cassava, Plantain and Rubber Based Land Use

Abstract: Protection of Soil Organic Carbon (SOC) and nitrogen (N) from losses is important in evaluation and maintenance of soil fertility and environmental quality. Uncertainties exist concerning the distribution of SOC pool and N in primary particle size fractions under land use types. A study was carried out to determine the distributions of SOC and N in sand, silt and clay fractions of a sandy soil under cassava, plantain and rubber land use types in southern Nigeria. Results showed that cassava had the highest amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The soil grain size directly affects the amount of organic carbon and total nitrogen it contains (Bechtold and Naiman, 2006;Pan et al, 2013;Udom, Benwari and Osaro, 2015). Zhou et al (2019) have showed that the total carbon (TOC) and nitrogen (TON) contents increase as the proportion of silt and clay fractions increases.…”
Section: Introductionmentioning
confidence: 99%
“…The soil grain size directly affects the amount of organic carbon and total nitrogen it contains (Bechtold and Naiman, 2006;Pan et al, 2013;Udom, Benwari and Osaro, 2015). Zhou et al (2019) have showed that the total carbon (TOC) and nitrogen (TON) contents increase as the proportion of silt and clay fractions increases.…”
Section: Introductionmentioning
confidence: 99%
“…This will strongly limit the organic matter accumulation in layers having particle sizes greater than 20 µm. This hypothesis is reinforced by many authors (Balesdent et al 2000;Voncir et al, 2006;Feyssa et al, 2011;Ratnayake et al, 2011;Guimares et al, 2013;Udom et al, 2015) who have demonstrated that organic matter renewal rate in coarse fractions is higher than in the fine fractions. The high mineralization rate of fresh soil organic matter observed in the present study, with high sand contents, is due to the fact that the bulk soil organic matter contents are always associated with fine particles which can physically protect them against microbial attacks (Feller, 1994).…”
Section: Soil Organic Carbon and Tn Distribution In Soil Organo-minermentioning
confidence: 89%
“…Soil fertility can be managed in several ways such as using organic or inorganic fertilizer, intercropping with legumes that fix nitrogen biologically such as beans and pigeon peas and crop rotation (Fung, Tai, Yong, Liu and Lam, 2019). Besides legumes, crops such as cassava improve soil properties through creation of biomass, enhancement of nitrogen and soil organic carbon which is beneficial to maize (Udom, Benwari and Osaro, 2015). In addition, depletion of nitrogen and phosphorus is low thus such crops could be intercropped or rotated with maize (Howeler, 2017).…”
Section: Introductionmentioning
confidence: 99%